Effect of Caffeine and Other Methylxanthines on Aβ-Homeostasis in SH-SY5Y Cells - Janitschke, Daniel (Biomolecules, 2019)
Methylxanthines (MTX) are alkaloids derived from the purine-base xanthine. Whereas especially caffeine, the most prominent known MTX, has been formerly assessed to be detrimental, this point of view has changed substantially. MTXs are discussed to have beneficial properties in neurodegenerative diseases, however, the mechanisms of action are not completely understood. Here we investigate the effect of the naturally occurring caffeine, theobromine and theophylline and the synthetic propentofylline and pentoxifylline on processes involved in Alzheimer’s disease (AD). All MTXs decreased amyloid-β (Aβ) level by shifting the amyloid precursor protein (APP) processing from the Aβ-producing amyloidogenic to the non-amyloidogenic pathway. The α-secretase activity was elevated whereas β-secretase activity was decreased. Breaking down the molecular mechanism, caffeine increased protein stability of the major α-secretase ADAM10, downregulated BACE1 expression and directly decreased β-secretase activity. Additionally, APP expression was reduced. In line with literature, MTXs reduced oxidative stress, decreased cholesterol and a decreased in Aβ1-42 aggregation. In conclusion, all MTXs act via the pleiotropic mechanism resulting in decreased Aβ and show beneficial properties with respect to AD in neuroblastoma cells. However, the observed effect strength was moderate, suggesting that MTXs should be integrated in a healthy diet rather than be used exclusively to treat or prevent AD.